(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors point out the increased intrusiveness and the high adaptability of Coleoptera Nitidulidae carpophagous to different environments and host-plants in important fruit and vegetable-grown areas in Italy. Pests species are mentioned by stressing the different noxiousness for the agricultural productions. Various aspects are pointed out, i.e. behaviour, time of appearance, present distribution in Italy, and damaged crops; suggestions for the possible adoption of contro! methods in order to reduce the pullulation are also reported. Finally a key is provided to facilitate the identification of the species currently mentioned as carpophagous.